Shift CTRL: Computing and New Media as Global, Cultural, Sociopolitical, and Ecological - Mullaney, Thomas S (Technology and culture, 2018)
We are living in a golden age for the study of information and language technologies in the modern period, and perhaps even more so for the study of computing and new media. Sustained by enduring engagements with Book History, Actor-Network-Theory, the Social Construction of Technology (SCOT) program, and Science, Technology, and Society (STS)—but also rejuvenated by concerns with cultural techniques, material semiotics, the aesthetics of bureaucracy, paperwork studies, media archaeology, neo-cybernetics, software studies, platform studies, and more—scholars have grappled with subject matter as diverse as the origins of the card catalog, the MP3 file format, French revolution-era paperwork and bureaucracy, xerography, TCP/IP protocol, spam, and more. Such variety conceals an underlying homogeneity, however. With important exceptions, recent studies have focused predominantly on the Western world, and within that, typically the English-language/Latin-alphabetic environment. By way of perspective, of the more than 120 titles published on five influential MIT Press series—"Inside Technology," "History of Computing," "Infrastructures," "Software Studies," and "Platform Studies"—only five focus in any sustained way upon Asia, the Middle East, or Africa. Meanwhile, in the relatively new yet highly influential "Electronic Mediations" series on the University of Minnesota Press, not a single monograph-length study deals with computing, gaming, or electronic mediation anywhere in the Non-Western world. In sharp contrast to the long tradition among Early Modernists of engaging with Non-Western information societies, then, once we reach the twentieth century, the world beyond Europe and North America almost ceases to exist.